1999
DOI: 10.1128/iai.67.2.899-907.1999
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a WaaF (RfaF) Homolog Expressed by Haemophilus ducreyi

Abstract: Haemophilus ducreyi lipooligosaccharide (LOS) is capable of inducing an inflammatory response in skin (A. A. Campagnari, L. M. Wild, G. Griffiths, R. J. Karalus, M. A. Wirth, and S. M. Spinola, Infect. Immun. 59:2601–2608, 1991) and likely contributes to the virulence of this sexually transmitted pathogen (B. A. Bauer, M. K. Stevens, and E. J. Hansen, Infect. Immun. 68:4290–4298, 1998). An open reading frame in H. ducreyi 35000 was found to encode a predicted protein that was 59% identical to the protein produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 80 publications
3
2
0
Order By: Relevance
“…However, in the temperature-dependent rabbit model, a lbgB (losB) mutant was as virulent as the parent strain, a result similar to our findings in humans (24). In the rabbit model, a gmhA mutant and a waaF mutant were less virulent than their isogenic parent (3,4). Although their LOS structures were not determined, the gmhA mutant probably produces an LOS composed of lipid A and KDO, while the waaF mutant makes lipid A-KDO-heptose.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, in the temperature-dependent rabbit model, a lbgB (losB) mutant was as virulent as the parent strain, a result similar to our findings in humans (24). In the rabbit model, a gmhA mutant and a waaF mutant were less virulent than their isogenic parent (3,4). Although their LOS structures were not determined, the gmhA mutant probably produces an LOS composed of lipid A and KDO, while the waaF mutant makes lipid A-KDO-heptose.…”
Section: Discussionsupporting
confidence: 83%
“…Although their LOS structures were not determined, the gmhA mutant probably produces an LOS composed of lipid A and KDO, while the waaF mutant makes lipid A-KDO-heptose. However, these truncated LOS mutants also exhibited changes in their outer membrane protein profiles relative to the parent, as has been reported for enteric deep rough lipopolysaccharide mutants (3,4).…”
Section: Discussionsupporting
confidence: 69%
“…A similar contiguous arrangement of the rfaC and rfaF genes was observed in Pseudomonas aeruginosa [17]. However, a recent paper on the characterization of rfaF homolog in Haemophilus ducreyi reported that rfaF gene was not located adjacent to other genes involved in LPS expression [18].…”
Section: Dna Sequence Analysis Of the Lps Biosynthesis Genesupporting
confidence: 56%
“…131 So far, all waaF genes cloned from various bacteria have been characterized by their ability to complement waaFdefective S. enterica strains as shown in silver-stained SDS-polyacrylamide gels. [132][133][134][135][136][137] WaaF-defective mutants were constructed and their Rd 2 -chemotype was confirmed either in SDS-gels, 133,135 in immunoblots with monoclonal antibodies against LPS or determined by mass spectrometry. 132,134,137 All mutants showed a fast migrating LPS in SDS-PAGE and an impaired virulence when tested in vivo.…”
Section: Single Steps Of Lps Biosynthesismentioning
confidence: 99%
“…132,134,137 All mutants showed a fast migrating LPS in SDS-PAGE and an impaired virulence when tested in vivo. 132,133,138 In P. aeruginosa it was not possible to generate waaC or waaF null mutants, indicating that P. aeruginosa is not viable with a deep-rough LPS. 136 The reason for this is unclear, but since it is known that the core region of P. aeruginosa is phosphorylated to an unusual extent, the lack of these negatively charged groups in deep-rough LPS could be responsible for this observation.…”
Section: Single Steps Of Lps Biosynthesismentioning
confidence: 99%